Progress in sintering technology of transparent polycrystalline alumina ceramics - Jun Yin; Xiao Li; Xi Zhang; Shengquan Yu; Yuanming Lai (Journal of Advanced Dielectrics)
As an important optical material, transparent polycrystalline alumina (PCA) ceramic is widely used in aerospace, high-temperature windows, medical due to its high strength, corrosion resistance, high hardness, and excellent stability at high temperatures. Since Al2O3 belongs to the crystal structure of the trigonal crystal system ([Formula: see text]), light is prone to birefringence when passing through the interior of the ceramic, and its transmittance is difficult to reach that of cubic crystal materials such as Y2O3 even under almost fully dense conditions. Using a special sintering process to decrease the sintering temperature and improve the real in-line transmittance of PCA ceramics has always been a research hotspot in related fields. In this work, a comprehensive review is made from the point of view of the sintering process based on the research status of transparent PCA ceramics in decades.